2021
DOI: 10.3390/biology10080792
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Involvement in Carbon Transformation via CH4 and CO2 in Saline Sedimentary Pool

Abstract: Methane and carbon dioxide are one of the most important greenhouse gases and significant components of the carbon cycle. Biogeochemical methane transformation may occur even in the extreme conditions of deep subsurface ecosystems. This study presents methane-related biological processes in saline sediments of the Miocene Wieliczka Formation, Poland. Rock samples (W2, W3, and W4) differed in lithology (clayey salt with veins of fibrous salt and lenses of gypsum and anhydrite; siltstone and sandstone; siltstone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Biodiversity analyses of microorganisms inhabiting various extreme environments like coal deposits [1,2,[18][19][20], groundwater [21][22][23], and subsurface petroleum reservoirs [24] have shown that methanotrophs are also a component of the subsurface microbiomes. Our previous research revealed that the Wieliczka Formation is the habitat of a methanotrophically active community [25][26][27]. We hypothesize that the rock surrounding the salt beds may serve as a new source of methanotrophic bacteria capable of efficiently degrading methane, thus with potential biotechnological application.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Biodiversity analyses of microorganisms inhabiting various extreme environments like coal deposits [1,2,[18][19][20], groundwater [21][22][23], and subsurface petroleum reservoirs [24] have shown that methanotrophs are also a component of the subsurface microbiomes. Our previous research revealed that the Wieliczka Formation is the habitat of a methanotrophically active community [25][26][27]. We hypothesize that the rock surrounding the salt beds may serve as a new source of methanotrophic bacteria capable of efficiently degrading methane, thus with potential biotechnological application.…”
Section: Introductionmentioning
confidence: 92%
“…4 kg) were extracted from freshly excavated surfaces of Wieliczka Formation sediments, immediately put into sterile plastic containers, and tightly sealed. Samples used for DNA extraction and microbial enrichment were externally sterilized by UV irradiation and flaming as previously described [26,31].…”
Section: Study Site and Samples Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, none of the previous studies attempted a detailed characterization of the microbial community of the environment. In the only study of Polish salt mines to use next generation sequencing (NGS) to date, Goraj et al ( 2021 ) describe the structure of the microbial community inhabiting halite and its importance for carbon transformation. In contrast, no studies have examined the brines from seepages and outflows in salt mines, nor have they assessed the biotechnological and pharmaceutical potential of the microbiota of Polish salt mines.…”
Section: Introductionmentioning
confidence: 99%